Study of monitoring concrete strength development using infrared thermography (IRT) - Mohd Shafiq, Mohd Zin (2017)
The purpose of this research study is to study the strength development and age of concrete by using Infrared Thermography (IRT) system. Infrared Thermography has been known and been established as one of reliable non-destructive test and faster tools in building structure investigating. Application of Infrared Thermography in non-destructive method has been popular in civil engineering world fields to detect voids and composition in concrete. With image processing system using IRT to access and evaluate concrete, checking and inspecting has becoming easier. Normal concrete cube specimen size (100mm x 100mm x 100mm) were prepared with grade on grade 30 and grade 40 for this research studies. IRT camera by FLIR product were used in IRT test for RGB (Red, Green, and Blue) image to be produce. This RGB image produced then being analysed and compared with compressive strength of the cube so that the correlation between RGB value and concrete age can be formed. All cube sample were tested in control condition where distance between sample of camera, temperature of room and sample, sample age and curing method variables where constant. Production of image using IRT camera needs to be handle with care and full with precaution as the lenses of IRT camera were very sensitive towards heat and thermal changes. Result of this research study showing that value of RGB will decrease as concrete age and strength increased. This conclude that correlation between RGB value and concrete strength development can be used for future studies.